6xx - 13x + 6 = 0 6x2 - 13x + 6 = 0 (3x-2)(2x-3)=0 3x-2=0 or 2x-3=0 3x=2 or 2x=3 x=2/3 or x=3/2 x=0.667 or x=1.5
18xxx-39xx-15xFactor out common factor (3x)3x(6xx-13x-5x)axx+bx+c3x(6xx-13x-5)a=6b=-13c=-5Multiply a and c:6*-5=-30Find multiples of ac that add up to b (d,e [ie de=ac, d+e=b]):-30=-1*2*3*5-30=-1*30, 1*-30-30=-2*15, 2*-15-30=-3*10, 3*-10-30=-5*6, 5*-6Rewrite axx+bx+c into axx+dx+ex+c:3x(6xx-13x-5)3x(6xx+x-30x-5)Factor sets of terms (ie axx+dx, and ex+c):3x(6xx+x-30x-5)3x(x(6x+1)-5(6x+1))Combine like terms:3x(x(6x+1)-5(6x+1))3x(x-5)(6x+1)
No. It is 9x, which is a monomial.
3x + 2 = 3x + 6 This is not possible.
4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified
3x + 11
The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.
3x-3x+4x^2+8x=4x^2+8x
6x + 8
It is equivalent to: 3x+6+5 = 3x+11
50, 53, 59
I think you mean (3x ± 1)^2 = (3x+1)(3x-1)?